Preliminary Study of Potential Bioimplant from Glycerol Plasticized Starch-Microcrystalline Cellulose Composite - Galih Rineksa; Yudan Whulanza; Misri Gozan (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2021)
Biodegradable and bio-based substitutes for conventional plastics are on the rise in these past decades. One of the applications of bioplastic is for biomedical implants or bioimplant. Starch was plasticized using glycerol at varying amounts (40% and 60% of dry starch mass) to produce thermoplastic starch (TPS). A reinforcement filler of microcrystalline cellulose (MCC) was used to improve the mechanical properties. The MCC content in this study was also varied (0%, 2%, 4%, and 8% w/w). This paper studies the mechanical properties of starch-MCC composites for their potential as bioimplant. The optimum glycerol and MCC contents from the results are 40% glycerol and 8% MCC with 2.97 MPa tensile strength and 7.20% strain at break. Thus, the sample has the potential application in bioimplant material for trabecular bone replacement, which has an average tensile strength of 2 MPa and strains at a break of 2.5%.